Selected Trends in Psychotherapy Research: An Index Analysis of RCTs - Rief, Winfried; Kopp, Melina; Awarzamani, Roya; Weise, Cornelia (Clinical Psychology in Europe, 2022)
Background: We wanted to analyze trends in psychotherapy research during the last decade. We used published randomized clinical trials (RCTs) that are cited in Web of Science (WoS) as an index for these activities. Method: We searched for RCTs published between the years 2010 and 2019. Search criteria included cognitive-behavioral treatments (CBT), e-mental health, Acceptance and Commitment Therapy (ACT), psychodynamic treatments, interpersonal therapy (IPT), schema therapy, systemic therapy, mindfulness treatments, and emotion-focused therapy (EFT). The numbers of publications for each treatment approach were accumulated for 5-year blocks (2010 to 2014; 2015 to 2019). Results: The search revealed 4,523 hits for the selected treatment options, of which 1,605 were finally included in the analysis. There was a continuous increase in published RCTs, with 68% more trials during the second five-year block. CBT (68%) and eHealth interventions (18%) show an increase in the number of studies, but there were no significant changes in its percentage in relation to all published RCTs. The next frequent treatments were ACT (4%), psychodynamic treatments (2%), IPT (2%), and mindfulness interventions (2%). We found a significant increase of the percentage of mindfulness (p = .008) and a significant decrease of the percentage of psychodynamic treatments (p = .02). Systemic (1.1%), emotion-focused (0.7%) and schema therapy (0.6%) represented smaller parts of published RCTs. Conclusion: A continuous increase of published RCTs underlines an active field of research on psychological interventions. Third wave treatments such as mindfulness increased their representation in research, while the part of psychodynamic treatments decreased.
CRIS-Team Scopus Importer:2024-03-27
Keywords: ACT; CBT; eHealth; mental health care; mindfulness; psychodynamic treatments; psychotherapy research; randomized clinical trials RCT; schema therapy; systemic therapy